PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Pada perusahaan Pertambangan yang terdaftar pada Bursa Efek Indonesia Periode 2016-2020) - Nuraini Nuraini,; Ina Ratnasari (Politeknik Negeri Lhokseumawe, 2022)
Abstract: The purpose of this study was to analyze the effect of profitability, liquidity and size of the board of commissioners on Corporate Social Responsibility disclosures. The data used in this study is the annual report of mining companies in 2016-2020. The sampling technique used in this study was purposive sampling, with multiple linear regression analysis using the SPSS version 25 program. The results showed that profitability partially had a positive effect on Corporate Social Responsibility Disclosures, while the Liquidity has no effect on Corporate Social Responsibility disclosure and simultaneously the profitability and liquidity have an effect on Corporate Social Responsibility disclosureKeywords: profitability , liquidity, CSR Disclosure